Quality improvement and antimicrobial stewardship in general practice – the role of the municipality chief medical officer. A qualitative study. (2nd July 2020) - Høye, Sigurd; Brænd, Anja Maria; Spehar, Ivan
Abstract: Aims: This study aimed to explore the conditions for the Municipal Chief Medical Officers' (MCMOs) involvement in quality improvement in general practice, specifically concerning antibiotic prescribing practices. Methods: This qualitative study consisted of semi-structured in-depth telephone interviews and group interviews with MCMOs ( n  = 12). The interview guide aimed to explore the MCMOs' views on their role and responsibilities regarding the quality of care in general practice. The data were analysed using systematic text condensation. Results: Three main themes were identified: 1) the relationship between the municipality and the general practitioner (GP), with the MCMO acting as an intermediary, 2) influencing the GPs' work and 3) antibiotic use and infection control. The MCMOs perceived themselves as liaisons between the municipalities and the GPs. They emphasized building trust, showing respect and sharing common values in their interactions with the GPs, upholding the GPs' professional autonomy. Working for quality improvement was considered a priority; however, MCMOs expressed a need for external support to establish a permanent quality improvement framework. The informants were positive about engaging in improving antibiotic prescribing practices because this combined the municipality's responsibilities for quality improvement and communicable disease control. Conclusions: The MCMOs considered themselves as well-suited agents for quality improvement in general practice, as liaisons between the municipalities and the GPs. Quality improvement in general practice would benefit from a clearer structure in terms of the MCMOs' roles and responsibilities. Within communicable diseases control, the MCMOs have a clear mandate, which places antimicrobial stewardship initiatives in a favourable position amongst other areas of quality improvement.